Value Relevance of Stakeholder Engagement: The Influence of National Culture. (30th September 2016) - Dal Maso, Lorenzo; Liberatore, Giovanni; Mazzi, Francesco
Abstract: Our study investigates whether stakeholder engagement is associated with a firm's valuation and the value relevance of accounting earnings. Since prior literature posits that the economic consequences of such practices may depend on the specific environment in which they are adopted, we also explore whether these associations are affected by the cultural traits of the country in which a firm operates. Based on a worldwide sample of firms for the period 2002 to 2014, we document that stakeholder engagement positively influences market‐to‐book value of equity, without enhancing the value relevance of firm's accounting earnings. Drawing on Schwartz's cultural framework, we show that the results hold only in countries with a low (high) level of embeddedness and hierarchy (mastery). Our study contributes to the literature exploring the economic consequences of non‐financial information and the importance of institutional characteristics for economic outcomes. Copyright © 2016 John Wiley & Sons, Ltd and ERP Environment